The Courage to Avoid “Safety Nets” in Theatre Costume Design. An Interview with LUCIAN BROSCĂŢEAN by TRENT M. SANDERS - SANDERS, Trent M. (Studia Universitatis Babeș-Bolyai Dramatica, 2018)
Through the years, Lucian has participated, with his fashion/art projects, at various national and international events: Romanian Fashion Week, Mercedes-Benz Berlin Fashion Week, International Fashion Showcase at London Fashion Week, MQ Vienna Fashion Week… He won several awards including: ‘Special Mention’ at the International Fashion Showcase London Fashion Week, Arts of Fashion ‘Wendy Jim and YKK’ Awards at MOMA San Francisco, Beau Monde Magazine’s ‘Crystal Globe’ for Best Romanian Designer, 3 times nominee for ‘ELLE Style Awards Romania’ Best Designer Category, 3rd place in the Fashion Design category and 42nd place in the general ‘Top 100 Cool Brands’ made by Forbes Romania.